Pembentukan Karangtaruna Desa Waijarang Sebagai Main Power Pemberdayaan Pemuda Oleh Mahasiswa KKNT-PPM Unwira 2022 - Lede Adju; Andriano G. Suban Yunior; Kornelius Laga Waleng; Yosefina Peni Bean; Agripina Alma Frida Paus; Ermilando Lobain; Leonardus Rivaldiy Ganggut; Maria Longa Pegan; Charles Bay Koda; Eko Rahaman Kadir; Chrisleman Adi Putra Amalo; Ulrikus Jeferius Naya; Frafilius Don Bosko Manu; Gracianus Edwin Tue P. Lejap (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Karangtaruna is a social organization that becomes the strength of young people in the village. Karangtaruna village by KKNT-PPM Unwira 2022 students is a community service that takes a special role in empowering village youth. The purpose of forming this Karang Taruna is a form of participation and concern for the problems faced by the village community. Activities carried out at the Waijarang Village Office, Nubatukan District, Lembata Regency provide many benefits. The benefits of youth activities, more specifically, must be a continuation of social groups with free creative space so that the planned and planned dynamic steps can be carried out properly. In addition, the formation of Karang Taruna has given a positive color in building the role of each young man and woman in preparing for this year's moment of independence.